2020
DOI: 10.20944/preprints202002.0452.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Reality Tremor Reduction in Parkinson's Disease

Abstract: Multidisciplinary neurotechnology holds the promise of understanding and non-invasively treating neurodegenerative diseases. In this preclinical trial on Parkinson's disease (PD), we combined neuroscience together with the nascent field of medical virtual reality and generated several important observations. First, we established the Oculus Rift virtual reality system as a potent measurement device for parkinsonian involuntary hand tremors (IHT). Interestingly, we determined changes in rotation were the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The virtual environment minimized hand tremors in all patients during the task. After the experiment ended, they noted a significant decrease in hand tremors in one of their patients with early PD [ 47 ]. Helmich et al studied the effects of motor imagery on Parkinson’s tremor patients.…”
Section: Discussionmentioning
confidence: 99%
“…The virtual environment minimized hand tremors in all patients during the task. After the experiment ended, they noted a significant decrease in hand tremors in one of their patients with early PD [ 47 ]. Helmich et al studied the effects of motor imagery on Parkinson’s tremor patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the system lacks flexibility and is not suitable for developing tremor rehabilitation training. J. Cornacchioli [20] studied the use of the Oculus Rift grip as a tool to detect Parkinson's symptoms by measuring involuntary hand movements. The study tested the effectiveness of Parkinson's symptoms and concluded that the accuracy of Oculus Rift was sufficient for measurement needs but did not develop the technology for tremor rehabilitation training.…”
Section: Introductionmentioning
confidence: 99%